A discussion with Herbert Giersch : current problems of the West German economy, 1976-1977 - Giersch, Herbert; American Enterprise Institute for Public Policy Research (Washington : The Institute, 1977)
This volume reports on the a discussion with Herbet Giersch, a public economist and director of the Kiel Institute for the World Economy on the problems of Western Germany economy,1976-1977.
Held on November 9, 1976 at the American Enterprise Institute for Public Policy Research, Washington, D.C.
Includes bibliographical references.
obn 22/01/2019
Loans
Keywords: Germany (West)